STABILITAS FISIK DAN AKTIVITAS KRIM W/O EKSTRAK ETANOLIK BUAH MAHKOTA DEWA (Phaleria macrocarph (scheff.) Boerl,) SEBAGAI TABIR SURYA - Hidayatu Hana Shovyana; A. Karim Zulkarnain (Faculty of Pharmacy, Universitas Gadjah Mada, 2013)
Cream of Ethanolic extract Mahkota dewa fruit (Phaleria macrocarph (scheff.) Boerl,) has been reported as a sunscreen in in-vivo. The objective of this study is to evaluate the activity of sunscreen and physical stability. Determination of sunscreen was done by defining values of SPF (Sun Protection Factor) using Switzerland Weber strain mice with in vivo method. In this test we used 1 group without treatment, one negative control group (base), and 4 group treatments. Group treatment is a cream w/o ethanolic extract Mahkota dewa fruit. The value of SPF is a comparison of the DEM on the skin which were given sunscreen cream with DEM on the skin without the cream. We also did some physical stability test on the cream such as the viscosity test, spreading power, latched power, and the ratio of segregation. The Data were analyzed using SPSS to find the effect for addition of extract and prolonged storage of stability of cream. The results showed that a cream Mahkota dewa at concentration 4.6, d and 10% have an activity as a sunscreen with an SPF value of 1.25; 1.56; 2.4; and 3.05. In addition the Mahkota dewa have a good physical stability during storage.